1974
DOI: 10.1007/bf02372777
|View full text |Cite
|
Sign up to set email alerts
|

The phytoseiid mitePhytoseius plumifer as a predator of the eriophyid miteAceria ficus [Acarina]

Abstract: The effects of the eriophyid mite Aceria ficus COTTE, the tetranychid mite Tetranychus arabicus ATTIAH and castor-oil pollen on the development and fecundity of the phytoseiid predator Phytoseius plumi[er (C. & F.) were studied. The feeding capacity of all developmental stages of P. plumi[er on A. fieus was also considered.A. ficus was noted to be the more preferable prey to the predator rather than T. arabicus. Pollen promoted a marked suppression in the predator's reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The last 2 predators were found to be effective on outdoor crops (Rasmy & Elbanhawy, 1974 ; Rasmy, 1977).…”
Section: Key-words : Phytoseiulus Persimilis Phytoseius Finitimus Amentioning
confidence: 99%
“…The last 2 predators were found to be effective on outdoor crops (Rasmy & Elbanhawy, 1974 ; Rasmy, 1977).…”
Section: Key-words : Phytoseiulus Persimilis Phytoseius Finitimus Amentioning
confidence: 99%
“…This species is reported in Mediterranean basin and has been observed in vineyards (Minarro and Kreiter 2012). Phytoseius finitimus is a natural enemy of Panonychus ulmi (Koch) (Duso and Moretto 1994), and eriophyid mites: Aceria ficus (Rasmy and El-Banhawy 1974), it can also feed on pollen (Rasmy and El-Banhawy 1975).…”
Section: Phytoseius Finitimus Ribaga 1904mentioning
confidence: 99%
“…On hollyhock and cotton pollen or sweet potato leaves, the immatures failed to develop to adulthood. Rasmy and Elbanhawy (1974) studied the effect of the eriophyid mite Aceria ficus Cotte, the tetranychid mite Tetranychus arabicus Attiah and castor-oil pollen on the development and fecundity of P. plumifer. They found that A. ficus was a more favourable prey for the predators than T. arabicus, and a doubling time (DT) of 3.43 days.…”
Section: Experimental Designmentioning
confidence: 99%
“…The predatory mite Phytoseius plumifer (Canestrini and Fanzago) is an important generalist indigenous predator of tetranychid and eriophyid mites on various crops in Iran (Kamali et al, 2001;Hajizadeh et al, 2002;Nadimi et al, 2009) as well as in other countries (Rasmy and Elbanhawy, 1974;Castagnoli and Liguori, 1985). Knowledge of the nutritional value of different plant pollens for P. plumifer is not only important for mass rearing of the mite, but also for a better understanding of its population dynamics in the field.…”
Section: Introductionmentioning
confidence: 99%